Rational emotive behavior therapy for reducing adolescent anxiety in post-covid-19 pandemic online learning: group approach and single case design - Dharma Tari, I Dewa Ayu Eka Purba; Mahaardhika, I Made (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The COVID-19 pandemic led to prolonged isolation and a widespread shift to online education, which has influenced students' emotional well-being. As schools transitioned back to in-person learning, many students exhibited signs of anxiety. Rational Emotive Behavior Therapy (REBT) is recognized as a promising method for addressing post-isolation anxiety by helping students develop rational thoughts and emotional regulation. This study explores the prevalence of anxiety among students involved in distance learning and examines the effectiveness of REBT in alleviating this anxiety. A single case design was employed with 6 students, selected from an initial group of 121 participants from five junior high schools in Denpasar, Indonesia. After filling out an anxiety questionnaire, 6 students were selected based on their anxiety levels and willingness to participate. These students underwent 12 REBT sessions, which included both group therapy and individual techniques. The analysis of pre- and post-test data revealed a significant reduction of 33.5% in anxiety levels, with statistical analysis showing a p-value of 0.025 (<0.05), confirming the positive impact of REBT. The study highlights the importance of addressing anxiety during transitions in education and underscores the potential of REBT in improving students' emotional well-being in post-pandemic learning environments. Further research can explore the long-term effects of REBT and its integration into school-based mental health programs.